Provisions on Waiting Periods in International Investment Protection Treaties and their Impact on the Jurisdiction of Arbitral Tribunals - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Provisions on so-called waiting periods in international investment protection treaties give an investor from one contracting state an opportunity to initiate arbitration against the host state provided that the time designated by the treaty from the date on which the dispute arose has elapsed. The aim of those provisions is to enable parties to the dispute to use this time for consultations and attempt to reach a negotiated settlement. The paper analyzes the attitude of contemporary arbitral practice towards the legal nature and effect of those provisions on tribunals’ jurisdiction in investment disputes. The analysis shows gradual and clear shift of position taken by the tribunals in cases in which claimants did not comply with waiting periods. Because arbitral tribunals today are more resolved to penalize premature submission of the dispute to arbitration than they were one decade ago, in the future one can expect much more cautious conduct of potential claimants in this regard.